EVALUASI PENCAHAYAAN PERPUSTAKAAN UNIVERSITAS MUHAMMADIYAH LAMONGAN BERBASIS PEMETAAN INTENSITAS CAHAYA SEBAGAI UPAYA MENGURANGI EYE FATIGUE - Vanis Aisyatul Ayu Sugiarti; Uswatun Chasanah; Latifatun Nur Aini; Rohmatul Badiyah (Journal of Health Management, Administration and Public Health Policies, 2024)
Libraries are an important aspect that universities have that involve lighting in their use. Meeting the needs of intensity in accordance with standards can help reduce vision problems, one of which is eye fatigue. The purpose of this study is to evaluate lighting in the library of the University of Muhammadiyah Lamongan.   The method of this research is to take a single data using a luxmeter and then the light intensity data obtained is mapped in the form of a contour map. The results of the study showed that the light intensity value in the library of the University of Muhammadiyah Lamongan had met the SNI of library lighting, which was in the range of 300 lux, because the average intensity value was >300 lux in both zones 1 and 2. The conclusion of this study is that the light intensity in the reading room of the University of Muhammadiyah library meets the SNI standard but still requires a light intensity value that can be used as a comparison so that the data obtained is more accurate, the data can be in the form of sensor measurement data or repeated measurements.